A Comparison of Humoral Immune Function in Response to a Killed Newcastle’s Vaccine Challenge in Caged Vs. Free-range Hy-line Brown Layers - Arbona, D.V.; Anderson, K.E.; Hoffman , J.B. (International Journal of Poultry Science, 2011)
The relationship between immune function and disease risk may be greatly influenced by an organism’s response to chronic stressors including those that are environmentally induced. Measurements of stress-induced immune alterations have previously been made in poultry species by utilizing hematological and immunological indices. To ascertain the effects of alternative layer housing management methods on humoral immune function, Hy-line Brown hens housed on range (n = 15) or in battery style cages (n = 20) were inoculated with a killed Newcastle′s vaccine. Blood serum samples were taken prior to injection and for three consecutive weeks following injection to assess antibody production. Antibody production was significantly higher in caged hens in comparison to free-range hens at pre-injection (1.69±0.70 vs. 0.069±0.069) (p<0.0001) and post-injection week one (2.26±0.77 vs. 0.145±0.25) (p<0.0001), week two (8.00±2.98 vs. 4.38±2.94) (p<0.001) and week 3 (9.24±2.56 vs. 6.69±3.86) (p<0.05). Additionally, caged hens exhibited a significantly higher level (p<0.0001) of total antibody production (5.30±0.23) throughout the immune challenge compared to free-range hens (2.82±0.26). Caged hens exhibited significantly higher H:L ratios (2.34±0.86 vs. 1.75±0.57) (p<0.05) during post-injection week 2 which correlated with the greatest difference in antibody production observed between the two groups of hens. This data indicated that environmental management methods utilized in layer hen production may influence both levels of humoral immune function and heterophil:lymphocyte ratios.